Lottery Prizes and Islamic Law Review on Mudharabah Savings Products at BMT Ar Roudloh Lamongan - Mun'im, Abdul; Ulum, Miftachul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
One of the efforts to increase customer appeal is by providing a prize draw. BMT Ar Raudloh in an effort to improve its services also applies a promotional strategy through the provision of a prize draw. The purpose of the study is to describe the review of Islamic law in the activities of determining, implementing a prize draw carried out at BMT Ar Roudloh in Lamongan. The triangulation method is used in describing the results of the research analysis and determining the validity of the data source. Informants in the study included managers, employees and customers. The results of the study indicate that the implementation of the prize draw activity starting from determining the requirements, participants and implementation has been in accordance with Islamic law. The implementation of the prize draw shows that the implementation of the prize draw does not conflict with Islamic law